Integrating single-cell RNA sequencing with multi-omics to decode disease microenvironments - Arti Devi; Vaibhav Pathak; Vagish Dwibedi; Jasdeep Singh; Ashish Kumar Pathak; Nancy George; Ashwani Kumar; Gursharan Kaur; Santosh Kumar Rath; Amit Chatterjee (Molecular Biology Reports, 2026)

A stable and potent buffalo EF1α1 promoter for robust gene expression in mammalian systems - Satarupa Dutta; Abhishek Das; Subhra Dutta; Amisha Bhattacharya; Goutam Ulgekar; Shankhamala Chatterjee; Amit Pal; Srimoyee Koner; Mariya Saify; Swarnali Khan; Soma Behera; Nirmalya Ganguli (Transgenic Research, 2026)

Effect of different phytoadditive mixtures on nutrient utilization, growth performance, milk production and fatty acid profile of Black Bengal goats - Amit Kumar Singh; Champak Bhakat; Upali Kisku; Muthupalani Karunakaran; Anupam Chatterjee (Tropical Animal Health and Production, 2026)

Enhancing landslide susceptibility mapping in the Himalayas: geospatial and machine learning with explainable AI (XAI) - Manas Utthasini; Idhayachandhiran Ilampooranan; Suraj Kumar Singh; Shruti Kanga; Pankaj Kumar; Krishnagopal Halder; Biswajeet Pradhan; Amit Kumar Srivastava; Ranit Sundar Chatterjee; Rabin Chakrabortty; Tarig Ali; Gowhar Meraj (Gondwana Research, 2026)

Role of non-timber forest products (NTFPs) in livelihood security of forest-fringe tribal communities in Purulia district of West Bengal - Amit Chatterjee; Sarfaraz Alam; Suvra Maji; Alok Sarkar (Agroforestry Systems, 2026)

Correction to: Perceptions and impacts of climate change in Central India: A study of tribal communities - Amit Kumar; Juna Probha Devi; Dhanya Bhaskar; Sulochana Shekhar; Uday Chatterjee; T. Mohanasundari (Theoretical and Applied Climatology, 2025)

Imidazopyrimidine-based pyruvate kinase M2 activator halts diabetic nephropathy progression via modulating epithelial-to-mesenchymal transition and fibrosis - Meenakshi Jain; Adil Ali Sayyed; Piyush Gondaliya; Saumya Kapoor; Deep Rohan Chatterjee; Rudradip Das; Kiran Kalia; Amit Khairnar; Amit Shard (Chemico-Biological Interactions, 2025)

Evaluating the impact of land use and land cover changes on air quality and human health in selected cities of West Bengal - Nikhil Nabik; Jaidul Islam; Amit Kumar; Uday Chatterjee; Basudeb Pyne (Environmental Geochemistry and Health, 2025)

Perceptions and impacts of climate change in Central India: A study of tribal communities - Amit Kumar; Juna Probha Devi; Dhanya Bhaskar; Sulochana Shekhar; Uday Chatterjee; T. Mohanasundari (Theoretical and Applied Climatology, 2025)

Spatial Heterogeneity in Health Risk Assessment of Heavy Metals During North-East Monsoon and South-West Monsoon over India - Martina Rani; Sakshi Ahlawat; N. Vijayan; Lokesh Yadav; Tirthankar Banerjee; Abhijeet Chatterjee; Manpreet Singh Bhatti; Trupti Das; Amit Dhir; Sangita Goel; Altaf Husain Khan; Ravindra Khaiwal; et al. (Aerosol Science and Engineering, 2025)

Selenium levels in colorectal cancer: A systematic review and meta-analysis of serum, plasma, and colorectal specimens - Amit Pal; Aninda Dhar; Muhammad Aaqib Shamim; Isha Rani; Ram Rattan Negi; Aaina Sharma; Namrata Chatterjee; Anmol Goyal; Sadashiv; Bandhan Kaur; Vincenzo Tondolo; Mauro Rongioletti; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

“Sustainability and Talent Management”: a Two-Pronged Approach for the Evolution of E-commerce in India - Manas Kumar Sarkar; Anindita Chatterjee Rao; Amit Kumar Singh (Circular Economy and Sustainability, 2024)

Mitochondria act as a key regulatory factor in cancer progression: Current concepts on mutations, mitochondrial dynamics, and therapeutic approach - Sraddhya Roy; Ananya Das; Aparajita Bairagi; Debangshi Das; Ashna Jha; Amit Kumar Srivastava; Nabanita Chatterjee (Mutation Research - Reviews in Mutation Research, 2024)

Unravelling the dynamics and causes of land subsidence in the National Capital Territory of Delhi, India, by spaceborne and in situ observations - R. S. Chatterjee; Pranshu Pranjal; Suresh Kannaujiya; Shailaja Thapa; Ashutosh Bhardwaj; Uma Kapoor; S. N. Dwivedi; Rajesh Chandra; Rajiv Kumar Srivastava; S. K. Singh; Harsh Kumar; Rajarshi Bhattacharjee; et al. (Bulletin of Engineering Geology and the Environment, 2023)

From trash to treasure: advancing the socio-ecological practice of rag picking for sustainable development in the Chandannagar town of Hooghly, West Bengal, India - Amit Kumar Das; Jenia Mukherjee; Uday Chatterjee (Socio-Ecological Practice Research, 2023)

The relationship between urban built environment and happiness in Bhopal, India - Sakshi Khare; Amit Chatterjee (Environment, Development and Sustainability, 2023)

Correction: Chlorogenic Acid: a Polyphenol from Coffee Rendered Neuroprotection Against Rotenone-Induced Parkinson’s Disease by GLP-1 Secretion - Nishant Sharma; Ritu Soni; Monika Sharma; Sayan Chatterjee; Nidhi Parihar; Mohd Mukarram; Ruhi Kale; Adil Ali Sayyed; Santosh Kumar Behera; Amit Khairnar (Molecular Neurobiology, 2022)

AMPK-dependent autophagy activation and alpha-Synuclein clearance: a putative mechanism behind alpha-mangostin’s neuroprotection in a rotenone-induced mouse model of Parkinson’s disease - Pathik Parekh; Nishant Sharma; Monika Sharma; Anagha Gadepalli; Adil Ali Sayyed; Sayan Chatterjee; Abhijeet Kate; Amit Khairnar (Metabolic Brain Disease, 2022)

Chlorogenic Acid: a Polyphenol from Coffee Rendered Neuroprotection Against Rotenone-Induced Parkinson’s Disease by GLP-1 Secretion - Nishant Sharma; Ritu Soni; Monika Sharma; Sayan Chatterjee; Nidhi Parihar; Mohd Mukarram; Ruhi kale; Adil Ali Sayyed; Santosh Kumar Behera; Amit Khairnar (Molecular Neurobiology, 2022)

Pre-to-post COVID-19 lockdown and their environmental impacts on Ghoghla beach and Somnath beach, India - Tarini Prasad Sahoo; Sonpal Vasavdutta; Amit Chanchpara; Nosad Sahu; Indirapriyatharsini Thiyagarajan; Sanak Ray; Shruti Chatterjee; Ravikumar Bhagawan Thorat; Soumya Haldar; Anil Kumar Madhava (Environmental Science and Pollution Research, 2022)

Importance–Performance Analysis to assess community role in solid waste management in the Hooghly District, West Bengal - Amit Kumar Das; Jenia Mukherjee; Uday Chatterjee (Innovative Infrastructure Solutions, 2022)

Benzaldehyde-induced developmental genotoxicity triggers both neural and non-neuronal cells including the cells of immunity in Drosophila melanogaster - Swapan Kumar Ghosh; Tridip Chatterjee; Sagarika Mitra; Amit Chakravarty; Sudipa Chakravarty; Ashim Kumar Basak (Biologia Futura, 2022)

Progress in understanding of Indian Ocean circulation, variability, air–sea exchange, and impacts on biogeochemistry - Helen E. Phillips; Amit Tandon; Ryo Furue; Raleigh Hood; Caroline C. Ummenhofer; Jessica A. Benthuysen; Viviane Menezes; Shijian Hu; Ben Webber; Alejandra Sanchez-Franks; Deepak Cherian; Emily Shroyer; et al. (Ocean Science, 2021)
Over the past decade, our understanding of the Indian Ocean has advanced through concerted efforts toward measuring the ocean circulation and air–sea exchanges, detecting changes in water masses, and linking physical processes to ecologically important variables. New circulation pathways and mechanisms have been discovered that control atmospheric and oceanic mean state and variability. This review brings together new understanding of the ocean–atmosphere system in the Indian Ocean since the last comprehensive review, describing the Indian Ocean circulation patterns, air–sea interactions, and climate variability. Coordinated international focus on the Indian Ocean has motivated the application of new technologies to deliver higher-resolution observations and models of Indian Ocean processes. As a result we are discovering the importance of small-scale processes in setting the large-scale gradients and circulation, interactions between physical and biogeochemical processes, interactions between boundary currents and the interior, and interactions between the surface and the deep ocean. A newly discovered regional climate mode in the southeast Indian Ocean, the Ningaloo Niño, has instigated more regional air–sea coupling and marine heatwave research in the global oceans. In the last decade, we have seen rapid warming of the Indian Ocean overlaid with extremes in the form of marine heatwaves. These events have motivated studies that have delivered new insight into the variability in ocean heat content and exchanges in the Indian Ocean and have highlighted the critical role of the Indian Ocean as a clearing house for anthropogenic heat. This synthesis paper reviews the advances in these areas in the last decade.

Benzoic acid treated Drosophila melanogaster: the genetic disruption of larval brain stem cells and non-neural cells during metamorphosis - Tridip Chatterjee; Swapan Kumar Ghosh; Shauvik Paik; Amit Chakravarty; Ashim Kumar Basak (Toxicology and Environmental Health Sciences, 2021)

Effect of reducing energy intake during the dry period on milk production, udder health, and body condition score of Jersey crossbred cows in the tropical lower Gangetic region - Amit Kumar Singh; Champak Bhakat; D. K. Mandal; A. Mandal; S. Rai; A. Chatterjee; M. K. Ghosh (Tropical Animal Health and Production, 2020)

Silver nanoparticle–induced developmental inhibition of Drosophila melanogaster accompanies disruption of genetic material of larval neural stem cells and non-neuronal cells - Ashim Kumar Basak; Tridip Chatterjee; Amit Chakravarty; Swapan Kumar Ghosh (Environmental Monitoring and Assessment, 2019)

Development of a machine vision system using the support vector machine regression (SVR) algorithm for the online prediction of iron ore grades - Ashok Kumar Patel; Snehamoy Chatterjee; Amit Kumar Gorai (Earth Science Informatics, 2019)

Serum selenium and pancreatic cancer: a prospective study in the Prostate, Lung, Colorectal and Ovarian Cancer Trial cohort - Sharmila Chatterjee; Gerald F. Combs; Amit Chattopadhyay; Rachael Stolzenberg-Solomon (Cancer Causes & Control, 2019)

Precise Segmentation and Classification of Epithelial Rete-Pegs Signature in Assessing Lower Limb Wound Healing Progression - Susmita Dey; Asmita Ray; Narayan Chandra Maiti; Provas Banerjee; Jyotirmoy Chatterjee; Santi Prasad Maity; Amit Roychowdhury; Ananya Barui (Journal of Medical and Biological Engineering, 2019)

Development of an expert system for iron ore classification - Ashok Kumar Patel; Snehamoy Chatterjee; Amit Kumar Gorai (Arabian Journal of Geosciences, 2018)

Groundwater arsenic contamination and its health effects in India - Dipankar Chakraborti; Mohammad Mahmudur Rahman; Bhaskar Das; Amit Chatterjee; Dipankar Das; Biswajit Nayak; Arup Pal; Uttam Kumar Chowdhury; Sad Ahmed; Bhajan Kumar Biswas; Mrinal Kumar Sengupta; Md. Amir Hossain; et al. (Hydrogeology Journal, 2017)

Development of machine vision-based ore classification model using support vector machine (SVM) algorithm - Ashok Kumar Patel; Snehamoy Chatterjee; Amit Kumar Gorai (Arabian Journal of Geosciences, 2017)

Ursolic Acid Loaded PLGA Nanoparticles: in vitro and in vivo Evaluation to Explore Tumor Targeting Ability on B16F10 Melanoma Cell Lines - Rinku Baishya; Dipak K. Nayak; Deepak Kumar; Samarendu Sinha; Amit Gupta; Shantanu Ganguly; Mita Chatterjee Debnath (Pharmaceutical Research, 2016)